A carbon nanotube wrapped Na3V2(PO4)2F3 cathode with a dual cation electrolyte: enhancing high-voltage stability and cyclability in zinc-ion batteries - Pandey, Priyanshi; Shivade, Rajkiran; Deshmukh, Ashvini; Shelke, Manjusha (Nanoscale, 2025)
Aqueous zinc-ion batteries (ZIBs) offer several compelling advantages as a safer and sustainable energy storage system. Polyanion-based cathodes, characterized by their comparatively higher voltage and structural stability, are promising for ZIBs. However, challenges hinder their practical applications, such as inferior rate capability and limited cycling stability. In this study, we constructed a carbon nanotube wrapped Na3V2(PO4)2F3 (NVPF-CNT) cathode integrated with a highly concentrated dual cation electrolyte (DCE) to enhance the electrochemical performance of ZIBs by enabling a synergistic Na+ and Zn2+ co-insertion mechanism. The DCE effectively regulates the solvation structure, stabilizes the solid electrolyte interface (SEI), minimizes free water molecules, thereby widening the electrochemical window and reducing the side reactions, and inhibits cathode dissolution. Consequently, the CNT-wrapped NVPF cathode exhibits an initial reversible capacity of 131.3 mAh g-1 at 0.05 A g-1, and retains 84% of its capacity over 500 cycles at 1 A g-1, with a nominal voltage of similar to 1.5 V. This approach offers valuable insights into the potential of CNT-wrapped NVPF cathodes in combination with a DCE while providing a comprehensive framework for advancing high-performance ZIBs.